Zagadnienia metodologiczne badań w klasach dwujęzycznych - Kaczmarek, Andrzej (Neofilolog, 2010)
The research in the field of bilingual education has had some specific aims and problems. First, we remind of the quest for the relation betweenbilingualism and intelligence. Then, we refer to some studies on classroom interaction. Finally, we present some projects focussing on the integration of learning content and language.